Towards an ethics of pronatalism in South Korea (and beyond) - Lee, J. Y. (Journal of medical ethics, 2025)
East Asian countries such as South Korea have recently made headlines for experimenting with different methods to incentivise people to have (more) children, in a bid to reverse declining birth rates. Many such incentives - child benefits, cash bonuses, dating events, and so on - appear morally innocuous at first glance. I will demonstrate in this analysis, however, that they amount to stopgap measures which reveal fundamental shortcomings with the way various nation states are approaching the so-called "problem" of fertility decline.